Analisis Pengambilan Keputusan dalam Kendala di UMKM Sadane Coffee - Fitri Rahmadani; Findi Maulana Hermawan; Andreas Saputra Sitanggang; William Tjandra (Indo Publishing, 2026)
This study aims to analyze business decision-making in overcoming various constraints faced by Sadane Coffee SMEs, particularly in labor management, capital, raw materials, and marketing aspects. The research method employs a qualitative approach with an explanatory survey design. Data were collected through direct observation and in-depth interviews with the business owner, supported by documentation and relevant literature studies. The results indicate that decision-making at Sadane Coffee SMEs remains simple and family-oriented. Labor management relies solely on family members, which helps reduce operational costs but limits production capacity. Business capital is entirely derived from personal funds without a clear separation between business and household finances, making financial performance evaluation difficult. Raw material management is relatively effective due to easy availability, although price fluctuations pose a significant risk. In terms of marketing, promotional activities are not conducted actively or systematically and mainly depend on word-of-mouth promotion and the owner's personal social media, resulting in limited market reach and weak branding. The study concludes that Sadane Coffee SMEs have considerable development potential; however, more strategic decision-making is required, particularly in utilizing digital promotion. The implications of this study highlight the importance of strengthening digital marketing strategies and improving business management to enhance competitiveness and sustainability of SMEs.